MORALITAS DALAM TEKS LAGU PADA ALBUM KATAKANLAH CINTA NAURA AYU: ANALISIS WACANA KRITIS - Karomah, Maulida Izzah; Parto, Parto; Poernomo, Bambang Edi (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2024)
The phenomenon currently occurring in Indonesia is the moral degradation of the nation's children. The decline in the morality of the nation's children is a problem that must be prevented immediately because it endangers the integrity of the Indonesian nation. One prevention effort is through song lyrics by instilling sociocultural-based moral values as socio-cultural-based moral education. This research analyzes the moral values and sociocultural values in the song lyrics on Naura Ayu's album Katakanlah Cinta and their use as critical response texts for junior high school students. Research overview, namely using qualitative research types and descriptive research designs. The data collection technique in this research is documentation of song lyrics transcribed via the YouTube channel. The research data is in the form of song texts for Naura Ayu's album Say Love Naura. The research results identified that the song texts in Naura Ayu's album Say Love contain moral values, namely caring for the environment, compassion, faith, tolerance, persistence and firmness. The sociocultural values contained are Indonesian natural resources, a culture of respecting mothers, a culture of respecting the family, a culture of peaceful living, a culture of fighting spirit, preventing a culture of bullying in Indonesia, and a culture of enthusiasm for achievement.